The East German state and the Catholic Church, 1945 - 1989 - Schäfer, Bernd (Studies in German history, 2010)
1945/1953: new structures in the postwar era -- 1953/1957: conflict and stabilization after the uprising -- 1957/1961: "building up socialism" -- 1961/1971: the GDR on the path to international recognition -- 1972/1989: the GDR as a sovereign state under international law